Hysteresis Based Quasi Fixed Frequency Current Control of Single Phase Full Bridge Grid Integrated Voltage Source Inverter - Lakshmi Syamala; Deepa Sankar; Suhara Ekkarakkudy Makkar; Bos Mathew Jos; Mathew Kallarackal (Energies, 2022)
The traditional Fixed Band Hysteresis Current Control (FB-HCC) though being widely used for the current control of grid integrated voltage source inverter (GI-VSI), has the drawback of variable switching frequency. To overcome this drawback, Complex Programmable Logic Device (CPLD) based switching scheme is proposed in this paper. The proposed method calls for a single reference wave and the control concept is to terminate the rising and falling inductor current (<semantics>iL</semantics>) either by the comparator or by the CPLD, based on the nature of its slope. Termination of the <semantics>iL</semantics> with steeper slope by the comparator ensures lower current ripple, whereas the CPLD ensures constant switching frequency (<semantics>fsw</semantics>). However, the <semantics>iL</semantics> obtained with the proposed logic has a DC offset, which is corrected by modifying the reference. The basic concept, switching logic, and reference correction are thoroughly detailed. MATLAB/Simulink results are included to verify the proposed concept. The constant frequency operation of the proposed method is also validated in a 2 kW, 230 V, 50 Hz GI-VSI prototype.